What Keeps Them Going, and What Gets Them Back? Older Adults' Beliefs About Physical Activity Maintenance. (5th July 2020) - Huffman, Mary Katherine; Amireault, Steve
Abstract: Background and Objectives: The overall purpose of this article was to investigate beliefs related to physical activity maintenance among adults aged 60 years or older. Research Design and Methods: Study 1 identified modal, salient behavioral, normative, and control beliefs using a free-response format. Study 2 was designed to gain a deeper understanding about these beliefs through in-depth semistructured interviews. Results: Findings indicate that perceived physical and emotional benefits, scheduling and having a physical activity routine, social support, and features of indoor and outdoor locations are facilitating of maintenance. Some beliefs appear more relevant to sustained engagement in physical activity, while others may be more helpful for reengagement after 1 week of inactivity. Discussion and Implications: This investigation raises new hypotheses for future research and provides insight for the use and adaptation of behavior change strategies that are potentially more acceptable and effective for the promotion of physical activity maintenance for older adults.